Novel Synthetic Chemistry of Ureas and Amides - Hutchby, Marc.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
In this thesis, the author investigates the chemistry and application of molecules containing urea and amide bonds. These bonds are some of the strongest known and are fundamental to biological processes. The author describes his discovery that sterically hindered ureas undergo solvolysis at room temperature under neutral conditions. This is a remarkable finding, since ureas are inert under these conditions and a general rule of chemistry is that hindered substrates are less reactive. Remarkably, the author translates these results to the correspondingly sterically hindered amides. This thesis has resulted in a number of outstanding publications in high profile journals. The unique method for breaking urea and amide bonds developed in this study is likely to have far reaching consequences for biological protein manipulation.
Transition metal catalysis -- Palladium catalysis -- Pd(II) catalysed aminocarbonylation of alkenes -- Carbonylation of aryl ureas -- Urea Hydrolysis -- Amide hydrolysis.
Keywords: Chemistry; Chemistry, Organic; Catalysis; Biochemistry; Chemistry; Organic Chemistry; Catalysis; Protein Science